Color and Marbling as Predictors of Meat Quality Perception of Argentinian Consumers - Testa, Maria Laura; Grigioni, Gabriela Maria; Panea, Begoña; Pavan, Enrique (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In Argentina, color and intramuscular fat are the main attributes of raw beef quality; however, it is necessary to clarify how consumers use them, in order to establish different marketing strategies. Consumer preferences are affected by multiple factors. Thus, the objective of the present study was to identify the Argentinian consumer’s choice behavior regarding beef color and fat content. An online survey was carried out in Argentina. It inquired about socio-demographic characteristics, purchase and consumption habits and beliefs, showing pictures related to color, marbling and the amount of fat. Choice behavior was evaluated by asking why consumers chose a particular picture out of the ones shown. Several Kruskal–Wallis tests evaluated the different hypotheses. Three different decision trees using the CHAID analysis method were created. Multifactorial analysis was carried out for clustering consumers. Regarding consumer beliefs, 90% of the respondents agreed with the sentence, “The two main characteristics defining beef quality at purchase time are meat color and marbling”. Socio-demographic characteristics affected purchase habits and beliefs; they also affected perceptions about meat color and marbling. It was possible to build three consumer groups for future marketing strategies: “hedonic” focused on a pleasing sensory experience, “appearance” prioritized the visual aspects, and the “health-conscious” consumers were interested in their healthy nutrition.